Hubungan Keikutsertaan Kegiatan Prolanis dengan Kualitas Hidup Lansia di Wilayah Kerja Puskesmas Bangkala - Musdalifah Musdalifah; Wardiah Hamzah; Alfina Baharuddin (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2024)
Chronic diseases cause disability in sufferers, so the Government, through BPJS Health, collaborates with health facilityservices to design a program known as “Chronic Disease Management Program” which is a system that combines management and communication if health services for participants with certain diseases through efforts to treat the disease independently. This research aims to determine the relationship between participation in Prolanis activitiesand the quality of life of the elderly. The type of research used is an analytical survey method using a Cross Sectional Study. The population in this study were 63 elderly who participated in Prolanis in the Bangkala Community Health Center working area. The sampling technique used was Exhaustive sampling. Data was collected through questionnaires and analysis using univariate and bivariate test, with a confidence level of α = 0.05. The research result show that reminders do not have a significant relationship with the elderly where the p value is 0.229. Monitoring health status has a significant relationship with the quality of life of the elderly where the p value is 0.033. Drug services do not have a significant relationship with the quality of life of the elderly where the p value is 0.214. Club activities have a significant relationship with the quality of life of the elderly where the p value is 0.047 based on the results of the chi-square test. Therefore, Bangkala Health Center Health officers are expected to pay more attention to reminder activities. Participants are also expected to carry out health status monitoring activities, drug services and club activities more regularly.